Speech recognition, loudness, and preference with extended bandwidth hearing aids for adult hearing aid users. (1st October 2020) - Van Eeckhoutte, Maaike; Folkeard, Paula; Glista, Danielle; Scollie, Susan
Abstract: Objective: In contrast to the past, some current hearing aids can provide gain for frequencies above 4–5 kHz. This study assessed the effect of wider bandwidth on outcome measures using hearing aids fitted with the DSL v5.0 prescription. Design: There were two conditions: an extended bandwidth condition, for which the maximum available bandwidth was provided, and a restricted bandwidth condition, in which gain was reduced for frequencies above 4.5 kHz. Outcome measures were assessed in both conditions. Study sample: Twenty-four participants with mild-to-moderately-severe sensorineural high-frequency sloping hearing loss. Results: Providing extended bandwidth resulted in maximum audible output frequency values of 7.5 kHz on average for an input level of 65 dB SPL. An improvement in consonant discrimination scores (4.1%), attributable to better perception of /s/, /z/, and /t/ phonemes, was found in the extended bandwidth condition, but no significant change in loudness perception or preferred listening levels was found. Most listeners (79%) had either no preference (33%) or some preference for the extended bandwidth condition (46%). Conclusions: The results suggest that providing the maximum bandwidth available with modern hearing aids fitted with DSL v5.0, using targets from 0.25 to 8 kHz, can be beneficial for the tested population.